The study of semi active suspension system on a half car model - 290005 Oh, Ngo Lim (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Automotif)) - Universiti Teknologi Malaysia, 2005